On the Theory of Economic Policy - Chipman, John S.; Tinbergen, J. (The Review of Economics and Statistics, 1954)
textabstractSerie "Contributions to Economic Analysis", No.1. In Spanish: Ensayos de Teoria Economica, Coleccion de Ciencias Sociales No. 42, Tecnos, Madrid, 1965, 71 p.